Time-dependent quantum mechanical calculations on the formation of molecular hydrogen on a graphite surface via an Eley-Rideal mechanism - Meijer, A; Farebrother, A; Clary, D; Fisher, A (2001)
The associative desorption of H2 (v,j) on a graphite(0001) surface via an Eley-Rideal mechanism has been studied theoretically. In our calculations we used a time-dependent wave packet method treating three degrees of freedom quantum mechanically. A newly developed potential energy surface based on plane-wave density functional calculations was employed. In our 3D calculations we find less vibrational excitation for the product H2 molecules than in calculations that used only two degrees of freedom. However, the product H2 molecules are formed rotationally excited. This could have important implications for the chemistry of H2 in the interstellar medium and the interpretation of astronomical data. © 2001 American Chemical Society.